1993
DOI: 10.1111/j.1471-4159.1993.tb03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Antisense GAP‐43 Inhibits the Evoked Release of Dopamine from PC12 Cells

Abstract: Abstract:To investigate the role of the neuronal growth-associated protein GAP-43 (neuromodulin, B-50, FI, P-57) in neurotransmitter release, we transfected PC I 2 cells with a recombinant expression vector coding for antisense human GAP-43 cRNA. Two stable transfectants, designated AS 1 and AS2, were selected that had integrated the recombinant sequence and expressed antisense GAP-43 RNA. Immunoblot analysis of proteins from AS 1 and AS2 cells indicated that the level of GAP-43 in these cell lines was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 37 publications
2
32
0
Order By: Relevance
“…15 We have previously shown that GAP-43 mRNA is highly expressed in monoaminergic neurons of adult rat brain 16 and phosphorylation of this protein has been linked to monoamine release. [17][18][19] We also found a high expression of GAP-43 mRNA in the limbic system of the adult rat including the amygdala and neo-cortex. 20 Similarly, in human brain, the transcript of GAP-43 is enriched in the cortex and limbic system.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…15 We have previously shown that GAP-43 mRNA is highly expressed in monoaminergic neurons of adult rat brain 16 and phosphorylation of this protein has been linked to monoamine release. [17][18][19] We also found a high expression of GAP-43 mRNA in the limbic system of the adult rat including the amygdala and neo-cortex. 20 Similarly, in human brain, the transcript of GAP-43 is enriched in the cortex and limbic system.…”
Section: Introductionmentioning
confidence: 68%
“…In fact, there is some evidence showing that reduction of GAP-43 inhibits the release of noradrenaline from cerebrocortical synapto-somes 17 and of dopamine from permeated synaptosomes 18 and P12 cells. 19 Although there are no data with respect to 5-HT release, one can hypothesize a similar involvement of GAP-43 in this monoaminergic system.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning transmitter function, phosphorylation of GAP-43 has been correlated with enhanced release (De Graan et al 1990b;Dekker et al 1990;Iannazzo 2001); overexpressing phosphorylatable GAP-43 in the presynaptic terminal is likely to alter this cellular function. Reductions in Ca ++ -evoked neurotransmitter release have been observed after levels of GAP-43 were reduced using antibodies (Hens et al 1995(Hens et al , 1998 or antisense oligonucleotides (Ivins et al 1993). Elevated GAP-43 transgene expression in hippocampal granule cells and protein in the mossy fiber terminal fields could thus enhance signal propagation through the hippocampal network, ultimately leading to enhanced memory function in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…After synaptogenesis, GAP-43 expression declines sharply in most neuronal populations except for those in specific association areas in the neocortex and limbic system Neve et al, 1988). GAP-43 is known to participate both in mechanisms of axonal pathfinding during neural development and in the regulation of neurotransmitter release and synaptic plasticity in mature synapses (Dekker et al, 1989;Aigner and Caroni, 1993;Ivins et al, 1993;Meberg et al, 1995;Strittmatter et al, 1995). Given the important biological properties of this protein, it is of great interest to define the mechanisms that control the developmental pattern and regional variations in GAP-43 gene expression.…”
mentioning
confidence: 99%